1991
DOI: 10.1126/science.1712985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deleting the R Domain on CFTR-Generated Chloride Channels

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR), which forms adenosine 3',5'-monophosphate (cAMP)-regulated chloride channels, is defective in patients with cystic fibrosis. This protein contains two putative nucleotide binding domains (NBD1 and NBD2) and an R domain. CFTR in which the R domain was deleted (CFTR delta R) conducted chloride independently of the presence of cAMP. However, sites within CFTR other than those deleted also respond to cAMP, because the chloride current of CFTR delta R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
4

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(176 citation statements)
references
References 27 publications
11
161
4
Order By: Relevance
“…Because deletion of the R domain activates the CFTR Clchannel [4,50], it has been suggested that a dephosphorylated R domain may effectively occlude the conducting pore of CFTR, analogous to "ball and chain" inactivation of the Shaker K + channel in Drosophila [51]. R domain phosphorylation may therefore cause a conformational change within the molecule, alleviating a steric blockade and thereby facilitating nucleotide-dependent channel regulation.…”
Section: Role Of R Domain Phosphorylationmentioning
confidence: 99%
“…Because deletion of the R domain activates the CFTR Clchannel [4,50], it has been suggested that a dephosphorylated R domain may effectively occlude the conducting pore of CFTR, analogous to "ball and chain" inactivation of the Shaker K + channel in Drosophila [51]. R domain phosphorylation may therefore cause a conformational change within the molecule, alleviating a steric blockade and thereby facilitating nucleotide-dependent channel regulation.…”
Section: Role Of R Domain Phosphorylationmentioning
confidence: 99%
“…Mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR) lead to dysfunction or absence of a cAMP regulated chloride channel in the apical membrane of epithelial cells. 1,2 Although various organs of the body are affected, respiratory failure is the cause of death in more than 95% of CF patients. Chronic inflammation, mucus accumulation and persistent bacterial infections cause a progressive decline in lung function.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus view is that the unphosphorylated R domain inhibits channel opening, an effect that is relieved by its phosphorylation. Rich et al (1991) discovered that channels that lacked large portions of the R domain were more active in the absence of PKA stimulation. Csanády et al (2000) subsequently showed that split CFTR molecules that lack the R domain and distal NBD1 (missing residues 634 -836) formed channels with opening rates in the absence of PKA that approached maximal opening rates for fully phosphorylated wild-type channels.…”
Section: Cftr Regulation By Pka Phosphorylationmentioning
confidence: 99%